2014
DOI: 10.3389/fncir.2014.00080
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intralimb adaptations to a sensory perturbation during activation of the serotonin system after a low spinal cord transection in neonatal rats

Abstract: Activation of the serotonin system has been shown to induce locomotor activity following a spinal cord transection. This study examines how the isolated spinal cord adapts to a sensory perturbation during activation of the serotonergic system. Real-time and persistent effects of a perturbation were examined in intact and spinal transected newborn rats. Rats received a spinal surgery (sham or low thoracic transection) on postnatal day 1 and were tested 9 days later. At test, subjects were treated with the serot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…In general, experience with ROM restriction depressed the frequency of forelimb steps during the period in which it was imposed for P1 and P10 subjects. This replicates a previous study, which showed that P1 subjects decreased their forelimb stepping behavior while suspended over a Plexiglas substrate [16], and a recent study showing that spinal cord transected P10 rats (low thoracic spinal cord transection happened at P1) decrease their stepping behavior as well [31]. …”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In general, experience with ROM restriction depressed the frequency of forelimb steps during the period in which it was imposed for P1 and P10 subjects. This replicates a previous study, which showed that P1 subjects decreased their forelimb stepping behavior while suspended over a Plexiglas substrate [16], and a recent study showing that spinal cord transected P10 rats (low thoracic spinal cord transection happened at P1) decrease their stepping behavior as well [31]. …”
Section: Discussionsupporting
confidence: 90%
“…Both real-time and persistent effects were observed in limb trajectories for P1 and P10 pups that received ROM restriction. This coincides with research in young humans and animals that shows that immature locomotor systems can adapt intralimb coordination to sensory feedback both during and after training [22, 29, 31, 32]. …”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations